Prawa człowieka w czasie konfliktu zbrojnego na tle problemu rozszerzania geograficznego zakresu stosowania międzynarodowego prawa humanitarnego oraz praw człowieka - Grzebyk, Patrycja (Polski Przegląd Stosunków Międzynarodowych, 2018)
The article firstly focuses on the relation between two branches of public international law i.e. International Humanitarian Law (Law of Armed Conflicts) and Human Rights Law especially in light of recent judgments of international tribunals. The author indicates main differences between IHL and HRL but also some similarities. Secondly, the article shows in what way IHL and HRL are broadening their geographic scope of application. Therefore the concept of “global armed conflict” and extraterritorial application of HRL are discussed. Thirdly, it shows what are the consequences of application of the IHL or the HRL standards in situation of armed conflicts. Finally, the article argues that it is possible and even necessary to harmonize those standards in light of de lege lata.